Corrupt local government as resource farmers : the helping hand and the grabbing hand - Engin Dalgic; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study the role of tax share and transparency of governance on growth and stagnation. A local government maximizes its private benefits using two activities. The first one consists of providing local public goods that help local firms to increase profits, thus enlarging tax revenue. The second one consists of extortion. We show that there is a threshold level of local government tax share, and a threshold level of transparency. Below these thresholds, the economy will stagnate and above them, the economy will achieve perpetual growth.
Keywords: H41; 330; corruption; growth; local government; tax share; Kommunalpolitik; Korruption; Lokales öffentliches Gut; Gemeindesteuer; Regionales Wachstum; Steuerbelastung; Theorie